State level water security indices in Mexico - Arreguin-Cortes, Felipe I.; Saavedra-Horita, J. Raul; Rodriguez-Varela, J. Manuel; Tzatchkov, Velitchko G.; Cortez-Mejia, Petronilo E.; Llaguno-Guilberto, Oscar J.; Sainos-Candelario, Arizabeth (Sustainable earth, 2020)
Background As tends to be the case in large, developing countries, Mexico is a nation of notable meteorological, hydrographic and social contrasts throughout its territory, which impact the various population strata in different ways. The public administration in Mexico is divided into federal (nationwide), state and municipal levels. In this sense, it is desirable to have water security metrics not only for the country as a whole but also for each state. The current paper seeks to show how these contrasts create different water-security scenarios using pertinent indices. This is particularly relevant for large countries such as Mexico, with approximately two-thirds of its territory in arid or semiarid areas, which face natural water scarcity, and only one-third has a very high relative water abundance. Results The concept of the global water security index was adapted to the state level in Mexico and calculated for each Mexican state in accordance with the worldwide analysis methodology proposed by other authors, which considers water availability, accessibility, safety and quality, as well as management. The proposed methodology was applied in a geographic information system environment, and it was used to obtain water security indices for all Mexican states. The states in which the situation was found to be critical, according to the computed global index, are Sonora, Baja California and Guanajuato, followed by Mexico City, Colima, Aguascalientes and Sinaloa. Conclusions Although the vast majority of the most vulnerable states and municipalities that have the highest drought risk are located in the north of the country in the Mexican highlands, even southern states such as Guerrero, Oaxaca, Chiapas, and Tabasco (which are typically characterized as rainy) have municipalities with a high drought vulnerability degree and are also severely affected by this phenomenon, especially in those years in which El Niño manifests itself, as was the case in 2015. The proposed methodology may serve as an example of how to assess water security using mainly free and officially published information, combined with international comparative country information, especially for countries where such information is limited.